GOALS OF PARTICIPATION IN PHYSICAL EDUCATION CLASSES - Rahim Ramzaninezhad; Farhad Rahmaninia; Mehr Ali Hemmatinezhad; Nooshin Benar; Misagh Hoseini Keshtan (Kharkov National Pedagogical University, 2011)
The importance of physical education in school life and for health points to the need to the better understands goal's participation of students in school education classes. This study was an attempt to investigate students' goals for participates in physical education (PE) classes. 455 random out of 72673 students of junior and senior high schools with the age range of 11 to 19 years (M=14.67). A 28-items survey was administrated to assess (a) demographics and (b) Purposes for Engaging in Physical Activity (PEPAS), on a 5-point Likert scale [23]. A panel of experts (n=10) reviewed the translated from of survey and provided feedback and comments on content validity of the instrument, and 50 student participated in pilot study. The analysis of the result indicated that the Individual development (the physiological efficiency and Psychic equilibrium) was rated the highest goal of participating in physical activity followed by the social interaction (the group interaction and cultural involvement) and the environmental coping (the spatial orientation and object manipulation). One-way Tukeys' post hoc comparison revealed significant difference between groups of subject differentiated on the basis gender age, Junior/senior high school, physical activity out of school, school team member ships, and physical activity on summer & holidays as Independent factors. The multivariate effect of these factors on some of the student's purpose was significant. The unvaried analyses showed that these factors had a significant effect on some of goals. These findings indicate the importance of ranking of students' purposes for engaging in PE classes. It is also necessary that these goals to be considered by the parents & teachers point of view.